Temperature-Insensitive Nonpolar Suspensions of Polyoxyethylene Alkyl Ether-Grafted Silica Nanoparticles - Chu, Cailing (Langmuir : the ACS journal of surfaces and colloids, 2024)
Nonpolar suspensions of organically modified particles exhibit a strong temperature sensitivity owing to the high-temperature-induced desorption/decomposition and the low-temperature-induced disorder/order conformational transition of the modifiers. This strong temperature sensitivity limits their applications, such as lubricants and oil-based drilling fluids, which require the suspensions to operate over a wide temperature range (e.g., 0-200 °C). We hypothesize that the introduction of a flexible ethylene oxide (EO) chain into the modifiers can disrupt the low-temperature-induced ordered conformation to improve the stability of the nonpolar suspensions. In this article, nonpolar suspensions with temperature insensitivity in the range of 5-160 °C were obtained via the covalent modification of silica NPs and the introduction of EO chains into the modifier molecules. Here, octadecyl-grafted silica NPs (C18-SiO2) and polyoxyethylene alkyl ether-grafted silica NPs (AEOn-SiO2) were synthesized and subsequently dispersed in mineral oil. The rheological properties of each suspension at different temperatures were evaluated, and the thermal stability of AEOn-SiO2 in mineral oil was investigated along with the conformational changes of the grafted chains. In the temperature range of 5-160 °C, the apparent viscosity and gel strength of the C18-SiO2 suspension changed dramatically, whereas the AEOn-SiO2 suspensions exhibited constant rheological properties over this temperature range. This temperature insensitivity of AEOn-SiO2 suspensions is attributed to the excellent thermal stability of AEOn-SiO2 in mineral oil and the disordered conformation of the EO chains upon cooling. This study provides a novel approach to preparing temperature-insensitive nonpolar suspensions, which have potential applications in the petroleum and lubricant industries